Ethiopia : Regionalization Study - World Bank (Washington, DC, 2013)
The study outlines the development strategy Ethiopia will need to pursue to achieve a balanced regional progress, and indicates some policy areas for attention, as the strategy develops. It examines the recent constitutional structure, government spending, and fiscal imbalances, including the capacity constraints the country faces, and governance issues. In addition, the role of municipalities under decentralized development is reviewed, suggesting policy reforms to develop higher levels of regional administration, to revise managerial procedures, and municipal tariffs, as well as to enhance municipal accountability in the standardization of the electoral process, to open citizen participation in municipal decision-making. The first part of the report focuses on federal-fiscal relationships, and related regional planning, and budgeting processes, and, argues that given the very substantial redistribution of funds taking place from the federal, to the regional level, the priority for policy design would be to look at the regional transfer system, to give incentives for regions to raise resources, thus contribute to development, and, consider stronger economic incentives in support of national programs. The second part covers municipal development, and gender issues, suggesting strategies to strengthen women's influence, and promote their issues at the regional, and community level.